Anaerobic cellulolytic rumen fungal populations in goats fed with and without Leucaena leucocephala hybrid, as determined by real-time PCR - Kok, Ching Mun (The Mircobiological Society of Korea, 2013)
The effect of Leucaena leucocephala hybrid-Bahru (LLB), which contains a high concentration of condensed tannins, on cellulolytic rumen fungal population in goats was investigated using real-time PCR. The fungal population in goats fed LLB was inhibited during the first 10 days of feeding, but after 15 days of feeding, there was a tremendous increase of fungal population (157.0 μg/ml), which was about fourfold more than that in control goats (39.7 μg/ml). However, after this period, the fungal population decreased continuously, and at 30 days of feeding, the fungal population (50.6 μg/ml) was not significantly different from that in control goats (55.4 μg/ml).